(3cJGH aj GdWHs - (3GdNGcj, GdCSdGbj, jMji Hf ESMGbs
(3ChdgG (B:s
(3SHMGf ef QbJ MceJg hQJHJg Ydi ebOeI hebGdJjf ; GdebOeI aj SHH JUfja GdcJGH GdebGdI GdChdi JfbSe Edi KdGKI aUhd GdaUd GdChd aj JYQja GdWHY s
(3BNQgG (B:s
(3hGdebOGQ efg OQge aj GdSMQ hjLQY GKQg ef GdeGA GdPj WHN ajg GdCUhd GdePchQI Ydi eG PcQfGg hjLH Gf jSJaQZ bHd GJNGPg hjJhbi HYOg ef GdeGA hGdTQGH hGdLeGY Je GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdWHs